A pre‐post intervention study: Knowledge among parents about child infections and antibiotic use facilitated by maternal and child health nurses. Issue 2 (12th September 2022) - Hansen, Matilde Bøgelund; Rasmussen, Ida Scheel; Marloth, Tina; Jarløv, Jens Otto; Arpi, Magnus; Mogensen, Dorthe; Jensen, Jette Nygaard
Abstract: Aims: To investigate parent's knowledge and beliefs of common infections and antibiotics in children before and after an educational intervention provided by maternal and child health nurses. Second, to investigate sociodemographic differences in parent's knowledge before and following the intervention. Design: A prospective pre‐post intervention study. The intervention consisted of a booklet with information about childhood infections delivered by maternal and child health nurses. Methods: The study population included 344 parents with a child born during 2017 and residing in three Danish municipalities. Knowledge about infections and antibiotics were collected quantitatively through an online questionnaire before and after the intervention (August 2017–November 2018) and analysed using linear mixed models. Results: Parental knowledge increased after the intervention. Parents with lower education and born in Denmark compared to parents with higher education and born in other countries experienced a higher increase in knowledge from baseline to follow‐up.